The Number of Armenians in the First Half of the 19th Century, According to the Data of Joseph Wolff - Bakhchinyan, Artsvi (ՀՀ ԳԱԱ «Գիտություն» հրատ.)
Joseph Wolff (1795–1862), a British missionary of German-Jewish origin, wrote six travel accounts about his journeys to Eastern countries. During these travels, he considered it necessary to record the populations of the various peoples living in the places he visited, including Armenians. In this respect, his travelogues constitute an exceptional source for clarifying the quantitative picture of the Armenian population in the first half of the nineteenth century, both in Eastern and Western Armenia, as well as in neighboring and other regions (the Ottoman Empire, Persia, the Middle East, Afghanistan, and India). In particular, in his works Missionary Journal of the Rev. Joseph Wolff, Missionary to the Jews and Researches and Missionary Labours among the Jews, Mohammedans, and other sects, by the Rev. Joseph Wolff, he recorded the number of Armenian inhabitants in the cities and villages he visited. Thus, according to his data, there were 8,000 Armenian families in Karabakh, 114 in Baku, 4,000 Armenians in Shapin-Garahisar, 5,000 in Sivas, 130,000 Armenians in Constantinople, 40 families in Kabul, 1,000 Armenians in British India, and so on. When noting the number of Armenian inhabitants in the cities and villages he visited, Wolff almost always distinguished between Apostolic and Catholic Armenians, and often found it necessary to indicate the number of clergy as well. Considering that Joseph Wolff, as a missionary, was in contact with Armenian ecclesiastical and educational figures and obtained his information from them, the data he provides may be regarded as at least largely reliable.
Keywords: History